Resectability of Rectal Neuroendocrine Tumors Using Endoscopic Mucosal Resection with a Ligation Band Device and Endoscopic Submucosal Dissection - Hong Kyu Lim; Seong Jun Lee; Dong Hoon Baek; Do Youn Park; Bong Eun Lee; Eun Young Park; Joon Woo Park; Gwang Ha Kim; Geun Am Song (Gastroenterology Research and Practice)
Background. Rectal neuroendocrine tumors NETs<10 mm in diameter, limited to the submucosa without local or distant metastasis, can be treated endoscopically. Endoscopic mucosal resection with a ligation band device (EMR-L) and endoscopic submucosal dissection (ESD) have been employed to resect rectal NETs. We evaluated and compared the clinical outcomes of EMR-L and ESD for endoscopic resection of rectal NETs G1<10 mm in diameter. Methods. We conducted a retrospective study of 82 rectal NETs in 82 patients who underwent either EMR-L or ESD. Therapeutic outcomes (en bloc resection and complete resection rates), procedure time, and procedure-related adverse events were evaluated. Additionally, we measured the distance of the lateral and vertical margins from the border of the tumor in pathologic specimens and compared the resectability between EMR-L and ESD. Results. Sixty-six lesions were treated using EMR-L and 16 using ESD. En bloc resection was achieved in all patients. The complete resection rate with EMR-L was significantly higher than that with ESD (95.5% vs.75.0%, p=0.025). The prevalence of vertical margin involvement was significantly higher in the ESD group than in the EMR-L group (12.5% vs. 0%, p=0.036), and ESD was more time consuming than EMR-L (24.21±12.18 vs. 7.05±4.53 min, p<0.001). The lateral and vertical margins were more distant in the EMR-L group than in the ESD group (lateral margin distance, 1661±849 vs. 1514±948 μm; vertical margin distance, 277±308 vs. 202±171 μm). Conclusions. EMR-L is more favorable for small rectal NETs with respect to therapeutic outcomes, procedure time, and technical difficulties. Additionally, EMR-L enables achievement of sufficient vertical margin distances.